Control of Mitochondrial Quality: A Promising Target for Diabetic Kidney Disease Treatment - Qi Li; Jin Shang; Reiko Inagi (Kidney International Reports)
Diabetic kidney disease (DKD) is the leading cause of end-stage renal disease (ESRD), affecting over 40% of patients with diabetes. DKD progression involves fibrosis and damage to glomerular and tubulointerstitial regions, with mitochondrial dysfunction playing a critical role. Impaired mitochondria lead to reduced adenosine triphosphate (ATP) production, damaged mitochondria accumulation, and increased reactive oxygen species (ROS), contributing to renal deterioration. Maintaining mitochondrial quality control (MQC) is essential for preventing cell death, tissue injury, and kidney failure. Recent clinical trials show that enhancing MQC can alleviate DKD. However, current treatments cannot halt kidney function decline, underscoring the need for new therapeutic strategies. Mitochondrial-targeted drugs show potential; however, challenges remain because of adverse effects and unclear mechanisms. Future research should aim to comprehensively explore therapeutic potential of MQC in DKD. This review highlights the significance of MQC in DKD treatment, emphasizing the need to maintain mitochondrial quality for developing new therapies.